PENGARUH MODEL PEMBELAJARAN GAME-BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V SD SWASTA TAMAN ASUHAN PEMATANGSIANTAR - Desi Gokma Manurung; Melvin M. Simanjuntak; Jon Roi Tua Purba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning models that are less varied, interesting, and not fully interactive, which lead to low student involvement in the learning process, result in low student learning outcomes. This study aims to determine the effect of the game-based learning model on student learning outcomes in the subject of science for grade V of SD Swasta Taman Asuhan Pematangsiantar. The research method is quantitative research. This study is a type of Pre-Experimental Design research with a One Group Pretest-Posttest Design design. Data were tested using SPSS Version 21. The results showed that the game-based learning model had a very significant effect on the learning outcomes of grade V students. Judging from the data results, the average pretest result was 57 and the posttest was 84.6. With the results of the hypothesis test analysis with a significance level = 0.05 and a t table of 2.064, the t count was 13.783. Thus, t count> t table = 13.783> 2.064, which means Ho is rejected and Ha is accepted. This provides the conclusion that the game-based learning model has a very significant effect on student learning outcomes.